Effect of Purslane powder and Zinc supplementation on the performance, egg quality, antioxidant system and liver histopathology of lead-exposed laying Quails - FARYADI, S.; SHEIKHAHMADI, A.; SADEGHI, A. (Journal of the Hellenic Veterinary Medical Society, 2020)
To determine effects of Purslane (Portulaca oleracea) and zinc supplementation in lead exposed quails, 180 adult female quails allocated into 9 groups. 1. Negative Control (NC, Fed with a corn-soy-based diet), 2. Cornsoy-based diet supplemented with 500 mg/kg lead acetate (Positive control), 3. Positive control supplemented with 0.5 % Purslane powder (PP), 4. Positive control supplemented with 1 % PP, 5. Positive control supplemented with 1.5 % PP, 6. Positive control supplemented with 140 mg/kg zinc, 7. Positive control supplemented with 0.5 % PP + 140 mg/kg zinc, 8. Positive control supplemented with 1 % PP + 140 mg/kg zinc, 9. Positive control supplemented with 1.5 % PP + 140 mg/kg zinc. Lead administration significantly decreased body weight, egg mass, egg production, liver weight, Haugh unit, serum concentrations of hematocrit, total protein, triglycerides and very low density lipoprotein concentration of quails (P<0.05). Serum alanine aminotransferase and lactate dehydrogenase activity significantly increased when compared with the NC (P<0.05). Superoxide dismutase and glutathione peroxidase activity in the liver and erythrocyte showed significant decrease (P<0.05). Lead administration resulted in a significant decrease (P<0.05) in total antioxidant capacity and increase in serum malondialdehyde. However, supplementation diet with 1.5% of PP reduced serum and liver malondialdehyde (P <0.05). Liver tissue of the birds in NC showed normal lobular architecture with central veins, radiating hepatic cords and portal triads, while this organ showed mild to severe tissue changes in lead exposed groups (P<0.05). It can be concluded that lead-exposure induced production of free radicals and weakened the antioxidant defenses of the quails. However, antioxidant status of quails partially improved when fed diets supplemented with 1.5 % PP and 140 ppm Zn.